Preparing systems codes for power plant conceptual design. (29th September 2021) - Morris, J.; Coleman, M.; Kahn, S.; Muldrew, S.I.; Pearce, A.J.; Short, D.; Cook, J.E.; Desai, S.; Humphrey, L.; Kovari, M.; Maddock, J.; Vaccaro, D.
Abstract: As power plant design programmes approach the transition between the pre-conceptual and conceptual design phases, the systems code PROCESS has been improved to incorporate more detailed plasma physics, engineering, and analysis modules. Unlike many systems codes, PROCESS combines the physics modelling with both technology and costs analysis. Some of the key topics in the conceptual design phase are toroidal field (TF) magnet design, divertor power handling, operational sensitivity, and economic uncertainty analysis. Models covering these areas have been integrated or improved in PROCESS. During pre-conceptual design, systems codes are an essential tool for exploring fusion power plant concepts. They allow one to model the interaction of the plant systems and quickly perform reactor optioneering. To be able to carry out these large scoping studies, the fidelity of the models can be restricted to reduce the computational time. For example, the EUROfusion EU-DEMO baseline designs are created using the systems code PROCESS and the ability to measure these trade-offs has led to important design choices being examined during the DEMO pre-conceptual design phase. Ruling out unfeasible designs allows one to efficiently identify where in the design space to carry out detailed design work. The paper describes how PROCESS has begun retooling for use in later stages of power plant conceptual design. Details are given for new additions to the PROCESS uncertainty quantification tools, high-temperature superconducting magnet model, TF coil model, and new models for spherical tokamaks (STEP). Additionally, the paper covers recent developments on the novel systems code BLUEPRINT, which is being used in both the EUROfusion and STEP projects. The paper concludes with an outlook on systems code activities at UKAEA and work with external partners.